2010
DOI: 10.1016/j.physbeh.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent antidepressant effects of lower doses of progesterone in rats

Abstract: Major depression is more prevalent among women than men, and progesterone might be involved in the mechanisms that generate these differences. Progesterone is clinically used for women in several reproductive events, but its antidepressant effect is unclear. Animal studies showed the interference of progesterone on depressive behaviors of rodents, but they are inconclusive, and no study compared different treatment durations. This study investigated the antidepressant effect of low doses of progesterone in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…Acute progesterone administration between pre-test and test FST sessions did not alter behavior both in intact female or male rats, while chronic treatment with progesterone (8–10 days) decreased depressive-like behaviors in female rats but increased immobility in males [139]. …”
Section: Preconditioning and Treatmentsmentioning
confidence: 99%
“…Acute progesterone administration between pre-test and test FST sessions did not alter behavior both in intact female or male rats, while chronic treatment with progesterone (8–10 days) decreased depressive-like behaviors in female rats but increased immobility in males [139]. …”
Section: Preconditioning and Treatmentsmentioning
confidence: 99%
“…Female rats were randomly selected to receive a daily intraperitoneal injection of 0.4 mg/kg body mass of progesterone or the vehicle, during 2 complete female oestrous cycles. Previous studies by our laboratory showed that the administration of this dose did not change the oestrous cycle of these rats (Andrade et al 2010). To determine the oestrous cycle of the female rats, vaginal smears were performed throughout the treatment period.…”
Section: Drugs and Experimental Proceduresmentioning
confidence: 99%
“…Only female rats having 2 regular 4-5 day cycles and that were in the diestrus II phase on the last day of the experiment were included in this study (n = 4 animals per group for the vehicle treatment and 5 animals per group for the progesterone treatment). On the last day of the experiment, all of the animals were exposed to the FST, which was performed as previously described (Andrade et al 2010). Briefly, on the first day of the treatment, the rats were exposed to a pretest session of 15 min.…”
Section: Drugs and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations